2022
DOI: 10.3390/cells11223548
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dynamic Metabolome of the HepG2 Cell Line: Rise and Fall

Abstract: Both biological and technical variations can discredit the reliability of obtained data in omics studies. In this technical note, we investigated the effect of prolonged cultivation of the HepG2 hepatoma cell line on its metabolomic profile. Using the GC × GC-MS approach, we determined the degree of metabolic variability across HepG2 cells cultured in uniform conditions for 0, 5, 10, 15, and 20 days. Post-processing of obtained data revealed substantial changes in relative abundances of 110 metabolites among H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Despite having similar genetic backgrounds, different examples of HepG2 cells (genetically modified or treated with various drugs and toxic agents) can display vastly different metabolic phenotypes [ 25 , 26 , 27 ]. Utilizing this variability could provide insights into the abnormal tumor metabolism and machinery of hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having similar genetic backgrounds, different examples of HepG2 cells (genetically modified or treated with various drugs and toxic agents) can display vastly different metabolic phenotypes [ 25 , 26 , 27 ]. Utilizing this variability could provide insights into the abnormal tumor metabolism and machinery of hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Nine datasets described situations in which cells were not subjected to explicit chemical or physical stimuli [ 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The article by Chun-Yun Zhang et al [ 31 ] is particularly interesting.…”
Section: Resultsmentioning
confidence: 99%
“…The smooth endoplasmic reticulum, mitochondrial number, amino acid, and cytochrome P450 levels of HepG2 cells are lower than normal liver cells. However, it is believed that the HepG2 cells retain a complete metabolic pathway, which is considered suitable for studying the cellular mechanism of liver lipid metabolism 36 . Our experiments used oleic acid to induce lipid accumulation in HepG2 cells before adding various concentrations of gypenoside XIII.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is believed that the HepG2 cells retain a complete metabolic pathway, which is considered suitable for studying the cellular mechanism of liver lipid metabolism. 36 Our experiments used oleic acid to induce lipid accumulation in HepG2 cells before adding various concentrations of gypenoside XIII. We found that gypenoside XIII improves triglyceride breakdown and contributes to reducing lipid accumulation in fatty liver cells.…”
Section: Effect Of Gypenoside XIII On Liver Inflammation In Mcd Diet-...mentioning
confidence: 99%
“…However, the lines were divided into two clusters at the transcript level: non-hepatic cell lines were grouped into one cluster and hepatic cells into another. Moreover, it can be assumed that the differences at the proteomic and metabolic levels will be more pronounced, especially given the differences observed between the passages of the HepG2 cell line [23].…”
Section: Discussionmentioning
confidence: 99%